Phytochemical screening and anticancer activity of leaf extracts of Physalis minima - Krishna Kumar, H. N.; Chauh, Jyoti Bala (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2016)
Physalis minima a medicinally important plant of the family Solanaceae has been screened for its anticancer activity. The results of preliminary phytochemical screening of the leaf extract revealed the presence of flavonoids, alkaloids, tannins, saponins, steroids, cardiac glycosides, reducing sugars and terpenoids. Determination of total phenolic contents revealed that methanolic extract showed 78.3 mg/g of phenolic compounds. Evaluation of total flavonoid content showed 61.3 mg/g of flavonoid. It was found that the % viability of HeLa cell line & Hep2 cell line are 80% & 71.8% respectively. The percentage of growth inhibition of methanolic extract in SRB assay was found to be increase with increasing concentration against both HeLa and Hep2cell lines (68 and 58% respectively). The methanolic extract showed the strongest growth inhibitory effect on both HeLa and Hep2 cell lines (85 and 73% respectively) in MTT assay. Flavonoids have been isolated and purified from the methanolic leaf extract.